Inhibition of Platelet GPVI Protects Against Myocardial Ischemia–Reperfusion Injury. Issue 4 (April 2016) - Pachel, Christina; Mathes, Denise; Arias-Loza, Anahi-Paula; Heitzmann, Wolfram; Nordbeck, Peter; Deppermann, Carsten; Lorenz, Viola; Hofmann, Ulrich; Nieswandt, Bernhard; Frantz, Stefan
Abstract : Objective—: The objective of this study was to investigate the effects of platelet inhibition on myocardial ischemia–reperfusion (IR) injury. Approach and Results—: Timely restoration of coronary blood flow after myocardial infarction is indispensable but leads to additional damage to the heart (myocardial IR injury). Microvascular dysfunction contributes to myocardial IR injury. We hypothesized that platelet activation during IR determines microvascular perfusion and thereby the infarct size in the reperfused myocardium. The 3 phases of thrombus formation were analyzed by targeting individual key platelet-surface molecules with monoclonal antibody derivatives: (1) adhesion (anti-glycoprotein [GP]-Ib), (2) activation (anti-GPVI), and (3) aggregation (anti-GPIIbIIIa) in a murine in vivo model of left coronary artery ligation (30 minutes of ischemia followed by 24 hours of reperfusion). Infarct sizes were determined by Evans Blue/2, 3, 5-triphenyltetrazolium chloride staining, infiltrating neutrophils by immunohistology. Anti-GPVI treatment significantly reduced infarct size versus control, whereas anti-GPIb or anti-GPIIbIIIa antibody fragments showed no significant differences. Mechanistically, anti-GPVI antibody–mediated reduction of infarct size was not because of impaired Ca 2+ signaling or platelet degranulation because mice deficient in store-operated calcium channels (stromal interaction molecule 1, ORAI1), α-granules (Nbeal2 −/− ), and dense granule release (Unc13d −/− ) had similar infarct sizes as control animals. Protective effects of anti-GPVI treatment were accompanied by improved microperfusion. Leukocyte infiltration was reduced in both anti-GPVI and anti-GPIb-treated IR mice. Conclusions—: Inhibition of platelet activation by an anti-GPVI antibody, but not inhibition of platelet adhesion or aggregation by an anti-GPIb or anti-GPIIbIIIa antibody significantly reduces infarct size. The reduction of the infarct size is primarily based on an improved microperfusion after anti-GPVI antibody treatment. Abstract : Supplemental Digital Content is available in the text.